1989
DOI: 10.1002/mrd.1120220302
|View full text |Cite
|
Sign up to set email alerts
|

Crater defect in human spermatozoa

Abstract: This report describes the "crater defect" in human spermatozoa, a malformation that consists of a nuclear and acrosomal invagination present in 100% of the cells, whereas tail structure and motility are fairly normal. The defect occurs during spermiogenesis. A possible concomitance with abnormalities in the microtubular apparatus involved in the sperm molding is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…This was true for patients with compromised semen parameters and for those either undergoing first or repeated ART attempts. In fact, more detailed morphologic observations by transmission electron microscopy, scanning electron microscopy, and confocal microscopy indicated that visible irregularities or vacuoles are almost ubiquitous in human sperm heads and even appear to be a paraphysiologic finding (35,(105)(106)(107). These vacuolelike structures or craters appear in >90% of spermatozoa from fertile donors with normal semen parameters (108,109).…”
Section: Quest For the Ideal Spermatozoonmentioning
confidence: 96%
“…This was true for patients with compromised semen parameters and for those either undergoing first or repeated ART attempts. In fact, more detailed morphologic observations by transmission electron microscopy, scanning electron microscopy, and confocal microscopy indicated that visible irregularities or vacuoles are almost ubiquitous in human sperm heads and even appear to be a paraphysiologic finding (35,(105)(106)(107). These vacuolelike structures or craters appear in >90% of spermatozoa from fertile donors with normal semen parameters (108,109).…”
Section: Quest For the Ideal Spermatozoonmentioning
confidence: 96%
“…It should be diagnosed because the consequences of poor acrosomal function can be bypassed using compounds that stimulate Ca 2+ fluxes within the oocyte during ICSI . Another rare acrosomal defect, the crater defect, was discovered owing to TEM's application; this anomaly is characterized by nuclear and acrosomal invagination detected in 100% of spermatozoa of the subject [Baccetti et al 1989]. …”
Section: Sperm Head Defectsmentioning
confidence: 99%
“…Sperm head, head-neck attachment, and flagellum are all regions that can be affected by systematic sperm defects. Globozoospermia or round head acrosome-less spermatozoa [Schirren et al 1971;Larson et al 2001], miniacrosome [Baccetti et al 1991], and a rare situation named 'crater defect' [Baccetti et al 1989] are all systematic defects of the sperm head. Defects of head neck attachment and acephalic sperm [Baccetti et al 1984;Chemes et al 1987a;Kamal et al 1999;Chemes and Rawe 2003], dysplasia of fibrous sheath (DFS) [Chemes et al 1987b;Chemes et al 1998;Sousa et al 2015], and primary ciliary dyskinesia (PCD) [Afzelius 1976;Escalier and David 1984;Chemes et al 1990;Baccetti et al 1993] are systematic defects of the head-neck attachment region and tail.…”
Section: Introductionmentioning
confidence: 99%
“…There are also reports on polyzoospermic subjects in whom a considerable decrease in total acrosin activity has been observed [16]. Nuclear invagination has also been reported to influence acrosome reaction and to reduce fertility [2].…”
mentioning
confidence: 98%